Enhancing Leave Management Systems with Design Thinking-Based UI/UX Development - Nur Fairus Ramadhanti; Achmad Sidik; M. Bucci Ryando (bit-Tech, 2025)
This study addresses the inefficiencies in the employee leave management process of a company operating in both the service and manufacturing sectors, which currently relies on a manual, document-based system devoid of centralized data integration. Such a system has led to administrative bottlenecks, documentation inaccuracies, and reduced operational transparency, thereby hampering employee satisfaction and organizational productivity. To overcome these limitations, the Design Thinking methodology was adopted as a user-centered approach for the development of an intuitive and functional web-based leave management application. The research employed the five phases of Design Thinking—empathize, define, ideate, prototype, and test—to ensure that the system's design aligns with user expectations and organizational goals. Primary data were gathered through interviews and questionnaires administered to employees and human resource personnel, enabling the identification of key pain points in the existing workflow. A prototype was developed and subsequently evaluated using the System Usability Scale (SUS), a widely accepted instrument for measuring perceived usability. The system achieved a usability score of 87.45% based on responses from 10 users, indicating a high level of user satisfaction and system acceptance. These findings demonstrate the effectiveness of the Design Thinking approach in producing a leave management system that not only enhances administrative efficiency but also fosters a positive user experience. The study contributes to the growing body of literature on user-centered system design and provides a replicable framework for organizations seeking to digitally transform HR administrative functions through iterative, human-centered design methodologies.